The People's Health (Newcastle-on-Tyne : North-East District Committee, Communist Party, 1943)
1943-10 1943 1940s 36 pages Second Session. A NATIONAL HEALTH SERVICE. Chairman: Councillor R.L. GOODWIN. The question of a National Health Service is very much to the fore these days. I think this is mainly due to the publication of the Beveridge Report, which is the most popular of all Government publications. Many workers regard the Beveridge Plan as something promised them during the war to keep them quiet. We can appreciate such a belief. That sort of thing has happened before. But the Plan is something which the workers must fasten upon and for which they must bring all possible pressure upon the Government. Much of our success will depend upon the trade unions. If they build up their organisation and centre their attention upon matters of practical value then they will be able to compel the Government to bring into being, a country really fit to live in. OPENING SPEECH. Councillor G.C. ESTHER (Organising Secretary Hospital and Welfare Workers Union). I think in the first place, I had better give a small amount of self explanation. I was invited as the speaker for this session because somebody believed I was the best man for the job. The fact I am here shows that I agreed. But I confess that I have considerable limitations and I am not a medical man. However, I do not regard this question as one merely for medical men. I would like it to be regarded as a question for every man and woman ; the medical men are merely incidental. I am not a member of the Communist Party. I am not here with any Party tie. I am here simply to say what I believe should be the position with regard to a National Health Service. In the first place in dealing with this vital question we must get down to fundamentals and we must face the fact that there is no possibility of a real National Health Service, in the fullest sense of that phrase, in the present system of society. Only under Socialism can we hope to get such a service. There are vested interests in our present health service — most reactionary and powerful interests such as the insurance companies who are interested in a health service, not for what it will give the people, but for what it will give them. There are the voluntary hospitals with their Hospitals Association ; big teaching schools, monopolies in chemical and in research departments. 21 15X/2/103/295